Association between antimicrobial usage and resistance in Salmonella from poultry farms in Nigeria - Jibril, Abdurrahman Hassan (2021)
Antimicrobial resistance (AMR) is a global health threat affecting treatment outcome in animals and humans. A pre-requisite for development of AMR reduction strategies is knowledge of antimicrobial use patterns, and how these affect resistance development. The aim of this study was to determine antimicrobial usage (AMU) and whether such usage was associated with AMR in Salmonella from poultry farms in Northwest Nigeria.